2020
DOI: 10.15244/pjoes/118746
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Heavy Metals (Zn, Pb, Cd) in <i>Polistes nimphus</i> (Christ, 1791) (Hymenoptera, Vespidae) Living on Contaminated Sites

Abstract: The aim of the study was to determine the extent of heavy metal accumulation (Zn, Cd and Pb) in the bodies of females of the predatory species Polistes nimphus (Christ, 1791) (Hymenoptera, Vespidae). The insects were captured in areas affected by the proximity of ZGH "Bolesław" -an industrial complex located in Bukowno near Olkusz (southern Poland), whose main activity is mining and processing of lead and zinc ores.Three sites that differed in terms of distance from the source of contamination and also in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
7
1
Order By: Relevance
“…The concentrations of heavy metal in our samples are similar to those reported in other insect species; e.g., in carabid beetles, the levels of Cd, Fe, and Pb were within a similar range [39] as our results, while Cu and Zn concentrations from our study exceeded those reported for the beetles. In a closer vespid relative Polistes nimphus wasps, bioaccumulation of Zn was higher than our results while Cd and Pb were lower [40]. Similarly, in P. dominulus, Pb concentration was lower than the concentration from our result, following similar trends from the polluted to the reference zone [41].…”
Section: Discussioncontrasting
confidence: 48%
“…The concentrations of heavy metal in our samples are similar to those reported in other insect species; e.g., in carabid beetles, the levels of Cd, Fe, and Pb were within a similar range [39] as our results, while Cu and Zn concentrations from our study exceeded those reported for the beetles. In a closer vespid relative Polistes nimphus wasps, bioaccumulation of Zn was higher than our results while Cd and Pb were lower [40]. Similarly, in P. dominulus, Pb concentration was lower than the concentration from our result, following similar trends from the polluted to the reference zone [41].…”
Section: Discussioncontrasting
confidence: 48%
“…The results presented in this article are an extension of part of the research by Mielczarek and Wojciechowicz-Żytko (2020).…”
Section: Introductionmentioning
confidence: 62%
“…The aim of the present study was to determine the fluctuating asymmetry (FA) of the first pair of wings of females of the predatory species Polistes nimpha (Christ, 1791 ) living in an environment contaminated with heavy metals (Zn, Cd and Pb).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations